Trends in congenital anomalies and associated factors among newborns in Eastern Ethiopia: an 8-year open cohort analysis of the Kersa Health and Demographic Surveillance System - Tesfaye Assebe Yadeta; Muluken Kumera Didisa; Yohannes Baye; Eyerusalem Tamiru; Gezaheng Mengesha; Lencho Kajela Solbana (BMJ Open)
Objective This study aimed to investigate the trends and factors associated with congenital anomalies (CAs) among newborns in Eastern Ethiopia from 2015 to 2022.Design Open cohort study.Setting The Kersa Health and Demographic Surveillance System (KHDSS), which is located in the Kersa district of the Oromia region in Eastern Ethiopia, covering 24 kebeles.Population Newborns registered at birth in the database of the KHDSS site in Eastern Ethiopia.Methods The KHDSS tracks demographic and health changes in the community. Newborn data were extracted using a checklist. Trends in CAs over time (in years) were analysed and the associated factors were identified through logistic regression analysis.Outcome measure Newborn CAs, which are structural or functional abnormalities present at birth, were assessed through thorough physical examinations and detailed interviews conducted by trained data collectors using a standardised questionnaire.Results Between 2015 and 2022, a total of 27 350 newborns were recorded in the KHDSS, 104 of whom had CAs. The overall rate of CAs was 3.83 per 1000 live births (95% CI 3.19, 4.61). There was a significant increase in the trend of CAs over the study period, with a Mantel-Haenszel χ2 of 82.76 (p=0.001). Factors associated with CA included maternal age over 35 years (adjusted OR (AOR)=1.68, 95% CI 1.07, 2.62), place of birth (AOR=2.04, 95% CI 1.04, 4.02) and normal birth weight (AOR=0.14, 95% CI 0.04, 0.47).Conclusion The data from the KHDSS revealed a rising trend in CAs. CA was associated with factors such as the mother’s age, place of birth and the baby’s birth weight. It is crucial for healthcare providers and stakeholders to consider these factors in efforts to reduce the prevalence of CAs.